Digital filters : principles and applications with MATLAB - Taylor, Fred J., 1940- (Hoboken, N.J. : Wiley, 2012)
'The proposed book is not an exposition on digital signal processing (DSP) but rather a treatise on digital filters. The material and coverage is comprehensive, presented in a consistent style that first develops topics and subtopics in terms it their purpose, relationship to other core ideas, theoretical and conceptual framework, and finally instruction in the implementation of digital filter devices. Each major study is supported by Matlab-enabled activities and examples, with each Chapter culminating in a comprehensive design case study'--Provided by publisher.
Includes bibliographical references and index.
Keywords: MATLAB; Electric filters, Digital; Signal processing -- Digital techniques -- Mathematics